2018
DOI: 10.1088/1361-6579/aac24a
|View full text |Cite
|
Sign up to set email alerts
|

Towards pulse rate parametrization during free-living activities using smart wristband

Abstract: The present study demonstrates that pulse rate parametrization using a consumer smart wristband is in principle feasible. The results show that the smart wristband is well suited for computing basic PRV parameters which have been reported to be associated with poorer health outcomes. In addition, the study introduces a methodology for the estimation of post-exercise heart recovery time and the heart's adaptation to physical workload during free-living activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(52 reference statements)
2
10
0
Order By: Relevance
“…We also observed the differences in PRV measured on the forearm and wrist even in the same arm [7]. Additionally, differing effects of body posture and exercise between PRV and HRV [8] and the variance of PRV caused by the effects of differing waveform on pulse wave fiducial point have been reported [9,10].…”
supporting
confidence: 62%
“…We also observed the differences in PRV measured on the forearm and wrist even in the same arm [7]. Additionally, differing effects of body posture and exercise between PRV and HRV [8] and the variance of PRV caused by the effects of differing waveform on pulse wave fiducial point have been reported [9,10].…”
supporting
confidence: 62%
“…The ACAT algorithm we used to detect CVHR has been developed and optimized for ECG RRI [11][12][13], but the present study indicated that the ACAT algorithm can also be used for PPG PI and performs as well as for ECG RRI. Many studies have reported discrepancies and non-substitution of pulse rate and heart rate variability [15][16][17][18][19], particularly in various diseases including sleep apnea [26]. Nonetheless, the present study showed equivalence of PPG and ECG in the detection of sleep apnea.…”
Section: Discussionmentioning
confidence: 43%
“…In a previous study of 862 subjects undergoing polysomnographic examination, the hourly frequency of CVHR detected by the ACAT algorithm showed a correlation coefficient of 0.84 with the apneahypopnea index (AHI) and detected subjects with AHI ≥15 with 83% sensitivity and 88% specificity [11]. Although studies of pulse interval (PI) variability have reported important differences in the amplitude of short-term fluctuation components from those of R-R interval (RRI) variability [15][16][17][18][19], ACAT algorithm may be robust to such differences because the CVHR wave period is long (25-130 s) and ACAT has ability to adapt the detection threshold according to the changes in CVHR amplitude. 2020 and May 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The ACAT algorithm we used to detect CVHR has been developed and optimized for ECG RRI [11][12][13], but the present study indicated that the ACAT algorithm can also be used for PPG PI and performs as well as for ECG RRI. Many studies have reported discrepancies and non-substitution of pulse rate and heart rate variability [15][16][17][18][19], particularly in various diseases including sleep apnea [27]. Nonetheless, the present study showed equivalence of PPG and ECG in the detection of sleep apnea.…”
Section: Plos Onementioning
confidence: 39%
“…In a previous study of 862 subjects undergoing polysomnographic examination, the hourly frequency of CVHR detected by the ACAT algorithm showed a correlation coefficient of 0.84 with the apnea-hypopnea index (AHI) and detected subjects with AHI �15 with 83% sensitivity and 88% specificity [11]. Although studies of pulse interval (PI) variability have reported important differences in the amplitude of short-term fluctuation components from those of R-R interval (RRI) variability [15][16][17][18][19][20], ACAT algorithm may be robust to such differences because the cycle length of CVHR is long (25-130 s) and ACAT has ability to adapt the detection threshold according to the changes in CVHR amplitude.…”
Section: Introductionmentioning
confidence: 99%